Place managers for crime prevention: the theoretical and empirical status of a neglected situational crime prevention technique - Douglas, Stephen (Crime prevention and community safety, 2020)
Place managers are individuals who are physically and legally able to prevent crime in proprietary places, in addition to their designated functions within these places. They can be apartment complex owners, store managers, bar owners, parking lot attendants, or other individuals who have ownership claims to a place or are employed by that place. Largely informed by the criminal opportunity perspective and recognized as a situational crime prevention technique, place managers benefit from a rich theoretical development, but only limited evaluation research. In examining the theoretical and empirical status of place managers, we were motivated to develop a greater understanding of the potential for place manager interventions to be implemented and evaluated, as well as to explore a promising mechanism—in the form of regulatory frameworks—to help place managers in performing roles related to the prevention of crime.